2021
DOI: 10.1111/rsp3.12384
|View full text |Cite
|
Sign up to set email alerts
|

Places that don't matter or people that don't matter? A multilevel modelling approach to the analysis of the geographies of discontent

Abstract: The possible impacts of contextual effects on political behaviour have long been studied and analysed by political scientists and geographers. We review previous relevant literature and extend it by incorporating the recent rise of populism and developments of socio‐economic determinants of the political economy of discontent and the geography of happiness and well‐being across the European Union. In particular, the research presented in this paper is aimed at analysing the impact of individual and contextual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In recent years there has also been a rapidly growing body of literature on a theme described as the geography of discontent, expressed through voting behaviour for extremist, populist and self-proclaimed anti-establishment parties (Dijkstra et al, 2019;Koeppen et al, 2021;McCann, 2020;Rodriguez-Pose, 2018). Although subjective happiness and well-being is not typically included in such studies, there is an underlying assumption that voting can be seen as a proxy for discontent, which we could argue is a component of happiness (or unhappiness!).…”
Section: What Makes Happy People Cities Regions and Countries? The De...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years there has also been a rapidly growing body of literature on a theme described as the geography of discontent, expressed through voting behaviour for extremist, populist and self-proclaimed anti-establishment parties (Dijkstra et al, 2019;Koeppen et al, 2021;McCann, 2020;Rodriguez-Pose, 2018). Although subjective happiness and well-being is not typically included in such studies, there is an underlying assumption that voting can be seen as a proxy for discontent, which we could argue is a component of happiness (or unhappiness!).…”
Section: What Makes Happy People Cities Regions and Countries? The De...mentioning
confidence: 99%
“…see a seminal article in this journal in 1988 by Ruut Veenhhoven and more recent work focusing on notions of 'guilt and discontent'; see Oxfevelt et al, 2017). More recently, discontent has also been conceptualised and analysed in relation to political voting behaviour in response to 'places left behind' (Dijkstra et al, 2019;Koeppen et al, 2021;McCann, 2020;Rodriguez-Pose, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Electoral geography approaches have made it possible to expand the traditional electoral sociology approaches (preponderance of the social classes' role in explaining electoral behaviors) and economic and psychological approaches. That is, electoral geography approaches consider the possibility that people's votes depend on their characteristics and on certain factors at the level of the territories in which they live (Johnston et al, 2014; Köppen et al, 2020). In particular, recent studies have shown that neglected areas have been fertile grounds for the rise of populism (Dijkstra et al, 2020; McCann, 2016, 2020; Rodríguez‐Pose, 2018).…”
Section: Geographical Roots Of Populism and Protestsmentioning
confidence: 99%
“…From an analytical point of view, the geography of discontent has been studied considering the link between regional economic performance and political implications, expressed with the recent growth of populism and votes of protest in discontinuity with respect to the past (Dijkstra et al, 2020). In examining the discontent of regional laggards, other authors (Díaz‐Lanchas et al, 2021; Koeppen et al, 2021) use individual and social data from the European Social Survey and the Eurobarometer and find the place‐based interplay between contextual and citizen's material conditions and subjective perceptions.…”
Section: Technology‐driven Development: Geographies Of Opportunity Or...mentioning
confidence: 99%
“…All this could contribute to the strengthening of negative reactions, discontent, forms of resistance by individuals, groups and places. Consequently, the new technological revolution could fuel negative perceptions of different levels of development and influence the geography of discontent, examined by the literature, which considers forms of intolerance and protest voting (McCann, 2020), but also subjective perceptions of prosperity and inequality extracted from the Eurobarometer (Koeppen et al, 2021) and online hate behaviours (Denti & Faggian, 2021).…”
Section: Introductionmentioning
confidence: 99%